THE MANAGEMENT QUALITY OF EDUCATION AT MADRASAH IBTIDAIYAH AL YUSUFIAH SUB-DISTRICT OF RANTAU SELATAN - Facruddin Azmi; Syaukani Syaukani; Maraya Monang Hasibuan (State Islamic University of North Sumatra Indonesia, 2020)
The purpose of this study is to describe: 1) Planning to improve the quality of teaching staff in Madrasah Ibtidaiyah Al Yusufiah, Rantau SelatanDistrict; 2) Organizing the improvement of the quality of teaching staff atMadrasah Ibtidaiyah Al Yusufiah, Rantau Selatan District; 3) Implementation of improving the quality of teaching staff at Madrasah Ibtidaiyah Al Yusufiah, Rantau Selatan District; and 4) Supervision of improving the quality of educators at Madrasah Ibtidaiyah Al Yusufiah, Rantau Selatan Sub-District . This study uses a qualitative approach with descriptive methods. Data collection uses interview, observation, and document study techniques. This research found that: 1) Planning for Improving the Quality of Educators at Madrasah Ibtidaiyah Al Yusufiah, Rantau Selatan District was done through identification, analysis, conceptualization and planning, determining plans, implementing plans, objectives, benefits, planning steps, planning stages, including indicators or quality targets to be achieved as a process of improving the quality of education. 2) Organizing Resources in Improving the Quality of Educators in Madrasah Ibtidaiyah Al Yusufiah Sub-District of Rantau Selatan carried out with a detailed process of all work and activities; 3) Implementation of the Teacher Quality Improvement Plan for Madrasah Ibtidaiyah Al Yusufiah District of Rantau Selatan Sub-District has not yet fully followed the stages of implementation of the general guidelines for implementation, because the concepts and objectives of the policy have not been fully understood by the policy actors as a result of the implementation of policy socialization which is somewhat less than optimal. 4) Supervision of Quality Improvement of Educators in Madrasah Ibtidaiyah Al Yusufiah Rantau Selatan Sub-District covers several stages, namely: supervision is carried out at the beginning as a tool to anticipate or initial steps towards obstacles and obstacles as well as deviations from the standards and objectives that have been prepared as well as tools correction before a program is completed. Keywords: Management, Quality Improvement, Implementation, Supervision